Aparaja revitalization: Lio ethnic oral tradition - C. AgeMaria Yulita (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
Oral traditions, as discourses told or passed down from generation to generation, include oral and written, all of which are passed on orally. Aparaja is a form of an oral tradition of the Lio ethnic community that needs revival. Aparaja is part of oral tradition in the form of traditional questions in the form of riddles. A parent or child has never spoken the Lio language puzzle in the Lio community. This is evident when people are asked questions about Aparaja, in general, they need to learn. Some parents sat they heard it but could not talk about it properly. This paper aims to explain the form and function of the Aparaja as the cultural wealth of the Lio ethnic community in two villages on the south coast of Ende Regency, namely Wolotopo and Ngalupolo villages. The approach used is the approach. Data collection techniques comprised interviews, recording, listening engagement, and note-taking techniques. The theories used are those of oral literature and those of reception.